2017
DOI: 10.3390/molecules22081328
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Michael Addition Organocatalyzed by α,β-Dipeptides under Solvent-Free Reaction Conditions

Abstract: The application of six novel α,β-dipeptides as chiral organocatalysts in the asymmetric Michael addition reaction between enolizable aldehydes and N-arylmaleimides or nitroolefins is described. With N-arylmaleimides as substrates, the best results were achieved with dipeptide 2 as a catalyst in the presence of aq. NaOH. Whereas dipeptides 4 and 6 in conjunction with 4-dimethylaminopyridine (DMAP) and thiourea as a hydrogen bond donor proved to be highly efficient organocatalytic systems in the enantioselective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 81 publications
0
17
0
Order By: Relevance
“…3-(2-Bromophenyl)-2,2-dimethyl-4-nitrobutanal ( 13ai ) [41]. Yellow oil (42 mg, 70%); 1 H NMR (CDCl 3 ): δ H = 9.55 (s, 1H), 7.61 (dd, J = 8.0, 1.2 Hz, 1H), 7.36–7.25 (m, 2H), 7.15 (ddd, J = 8.0, 6.8, 2.2 Hz, 1H), 4.84 (dd, J = 13.2, 11.3 Hz, 1H), 4.72 (dd, J = 13.2, 4.1 Hz, 1H), 4.62 (dd, J = 11.3, 4.1 Hz, 1H), 1.17 (s, 3H), 1.09 (s, 3H) ppm; 13 C-NMR (CDCl 3 ): δ C = 203.9, 135.7, 134.0, 129.6, 128.5, 128.0, 127.2, 76.6, 49.2, 45.4, 21.1, 18.9 ppm; HPLC: Chiralcel OD-H, λ = 230 nm, n -hexane/2-propanol, 80:20, 1.0 mL/min, t r ( major ) = 10.5 min, t r ( minor ) = 25.6 min.…”
Section: Methodsmentioning
confidence: 99%
“…3-(2-Bromophenyl)-2,2-dimethyl-4-nitrobutanal ( 13ai ) [41]. Yellow oil (42 mg, 70%); 1 H NMR (CDCl 3 ): δ H = 9.55 (s, 1H), 7.61 (dd, J = 8.0, 1.2 Hz, 1H), 7.36–7.25 (m, 2H), 7.15 (ddd, J = 8.0, 6.8, 2.2 Hz, 1H), 4.84 (dd, J = 13.2, 11.3 Hz, 1H), 4.72 (dd, J = 13.2, 4.1 Hz, 1H), 4.62 (dd, J = 11.3, 4.1 Hz, 1H), 1.17 (s, 3H), 1.09 (s, 3H) ppm; 13 C-NMR (CDCl 3 ): δ C = 203.9, 135.7, 134.0, 129.6, 128.5, 128.0, 127.2, 76.6, 49.2, 45.4, 21.1, 18.9 ppm; HPLC: Chiralcel OD-H, λ = 230 nm, n -hexane/2-propanol, 80:20, 1.0 mL/min, t r ( major ) = 10.5 min, t r ( minor ) = 25.6 min.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Juaristi and co-workers considered six noveldipeptides 83 a-f as potential chiral organocatalysts in the asymmetric Michael addition (Scheme 61). [83] Initial studies revealed that for the Michael addition of N-arylmaleimides as substrates, catalyst 83 b could afford better yield and selectivity with NaOH as a base additive than other organocatalyst based α,α-dipeptide under neat condition (Scheme 61A). Furthermore, to examine the effect of solvent the reaction was conducted in solution and only dichloromethane afforded results comparable in yield and selectivity relative to the neat conditions.…”
Section: Asymmetric Michael Reactionmentioning
confidence: 99%
“…In 2017, Juaristi and co‐workers considered six novel‐dipeptides 83 a – f as potential chiral organocatalysts in the asymmetric Michael addition (Scheme ) . Initial studies revealed that for the Michael addition of N ‐arylmaleimides as substrates, catalyst 83 b could afford better yield and selectivity with NaOH as a base additive than other organocatalyst based α,α‐dipeptide under neat condition (Scheme A).…”
Section: Solvent‐free Reactions In Asymmetric Catalysismentioning
confidence: 99%
“…Amino acids are well-known as safe and green ligands for preparing asymmetric catalysts [7][8][9][10], such as proline/cyclobutane which used in asymmetric aldol additions, amino acid-containing peptide organocatalysts applying in asymmetric Michael addition [11], and conjugate addition reactions of aldehydes to maleimide [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%